2018
DOI: 10.1049/iet-epa.2017.0525
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of interior‐mount LSPMSM under asymmetrical stator winding

Abstract: Reliable and safe operation of electric motors in the industry is highly desirable. Accurate modelling is the first step in developing a diagnostic tool for different types of failures. This study presents a generalised dq-model for interior-mount line start permanent magnet synchronous motors under asymmetrical stator phase's windings. The presented dq-model has been derived using winding theorem. Implementation and simulation of the derived dq-model has been done using MATLAB/ SIMULINK software. For validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Figure 6 shows the circuit diagram of the test. Based on the circuit analysis, the resistance r s and the leakage inductance L ls can be calculated by using Equations (12) and (13), respectively, as follows: Using Equations (2) and 3, the applied phase voltage (V φ ), the corresponding current ( I φ ) and the phase shift ( θ ) between them are required to calculate the stator resistance and the leakage inductance. Therefore, an AC power supply, ammeter, voltmeter, CASSY unit, and a computer were used to perform the test as shown in Figure 7.…”
Section: Single Phase Ac Test (Rotor Not Included)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows the circuit diagram of the test. Based on the circuit analysis, the resistance r s and the leakage inductance L ls can be calculated by using Equations (12) and (13), respectively, as follows: Using Equations (2) and 3, the applied phase voltage (V φ ), the corresponding current ( I φ ) and the phase shift ( θ ) between them are required to calculate the stator resistance and the leakage inductance. Therefore, an AC power supply, ammeter, voltmeter, CASSY unit, and a computer were used to perform the test as shown in Figure 7.…”
Section: Single Phase Ac Test (Rotor Not Included)mentioning
confidence: 99%
“…In addition, it is invaluable that the electric machine manufacturers and designers perform various simulations and analysis before the prototypes are made. Several researchers have carried out several simulation and experimental works on parameter estimation [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, ASW has attracted much attention [16][17][18][19][20], and many researchers have defined ASW as one of the faults in the motor. Massimo et al [16] analysed the influence of ASW on magnetic motive force harmonic content, cogging torque, iron core loss and operation performance of a permanent magnet synchronous motor (PMSM).…”
Section: Introductionmentioning
confidence: 99%
“…Massimo et al [16] analysed the influence of ASW on magnetic motive force harmonic content, cogging torque, iron core loss and operation performance of a permanent magnet synchronous motor (PMSM). Maraaba et al [17] proposed a generalised dq-model derived using winding theorem for an interior-mount line-start PMSM (LSPMSM) under ASW, and investigated the torque frequency spectrum. Zagirnyak et al [18] demonstrated that the ASW influence on dynamic and power characteristics of an electric drive with vector control, and presented two structures of IM control systems.…”
Section: Introductionmentioning
confidence: 99%
“…In general, electrical motor failures can be categorized into electrical and mechanical faults [4]. Electrical faults/asymmetries can be further categorized into rotor and stator faults.…”
Section: Introductionmentioning
confidence: 99%